Assault-related traumatic brain injury hospitalizations in Canada from 2010 to 2021: rates, trends and comorbidity - Shikha Saxena; Sarah Zutrauen; Steven R. McFaull (BMC, 2024)
Abstract Background Traumatic brain injury (TBI) is a major cause of morbidity and mortality globally. TBI is often associated with other physical or psychological issues resulting in high hospitalization costs. TBI incidence and recovery can vary with the external cause being intentional or unintentional. It is important to monitor the rates of TBI hospitalizations related to different external causes. This study examined the annual rate, comorbidity and length of stay associated with assault-related TBI hospitalizations and compare it with other external causes, by age and sex in Canada from 2010 to 2021. Methods Discharge Abstract Database was used to extract cases of TBI (2010-2021). ICD-10-CA codes were used to classify all cases with TBI as per assault and other external causes (falls; transport; sport, physical activity and recreation; struck by). Additional variables, including age, sex, comorbidity and length of stay, were examined. Time trends were quantified using Joinpoint regression. Results The average annual percent increase for all TBI hospitalizations from 2010 to 2021 was not significant at 0.1%. Females accounted for 35.8% of these TBI hospitalizations. From 2010 to 2021, assault-related TBI hospitalizations showed a significant annual decline of 4.1% for males and a significant increase of 1.2% for females. Increase in TBI hospitalizations related to falls showed an average annual percent increase of 1.4% for males and 2.2% for females. A significant decrease was observed for TBI hospitalizations related to the other three (transport, SPAR and struck by) external causes for both sexes from 2010 to 2021. Infants and children under 10 years of age had higher percentages of cases with comorbidities and higher length of stay for assault-related TBI hospitalizations. Conclusions Assault-related TBI hospitalization rates decreased overall and among males, rates among females increased from 2010 to 2021. These results underscore the importance of targeted prevention efforts for TBI related to different external causes, age and sex, and continued surveillance to monitor the epidemiology of assault-related TBI.